Stormwater Discharge Management: A Practical Guide to Compliance - Spellman, Frank R.; Drinan, Joanne E. (Government Institutes, 2003)
This comprehensive resource provides engineers, managers, compliance specialists, construction professionals, and students with the tool they need to understand and comply with the requirements of the Code of Federal Regulations (CFR) Title 40 Chapter 122 stormwater regulations. Stormwater Discharge Management covers the full spectrum of stormwater issues, including stormwater regulations, NPDES permitting, minimum control measures, activities-based discharges, overflows, stormwater monitoring, stormwater enforcement strategy, and the new Stormwater Phase II Rule, which mandated compliance March 10, 2003. Readers will learn who meets the criteria for compliance under this rule and how compliance can be achieved in construction activity, agricultural activity, and marine activity. To help simplify the process, the authors identify each and every compliance requirement, from examining the different types of stormwater discharge permits to writing an effective Stormwater Pollution Prevention Plan (SWPP). They also include actual EPA field enforcement practices and best management practices to help readers ensure compliance success. Readers will gain a clearer appreciation for the stormwater regulations by reviewing the objectives of the Clean Water Act, the purpose and requirements of the National Pollutant Discharge Elimination System (NPDES), and the types of discharges/facilities affected by the laws.